Technology sovereignty: From demand to concept; Technologiesouveränität: Von der Forderung zum Konzept - Jakob Edler; Knut Blind; Rainer Frietsch; Simone Kimpeler; Henning Kroll; Christian Lerch; Thomas Reiss; Florian Roth; Torben Schubert; Johanna Schuler; Rainer Walz (Fraunhofer-Institut für System- und Innovationsforschung ISI, 2020)
Calls for technology sovereignty in Europe were becoming louder even before the current Corona crisis. Growing geopolitical uncertainties and the threat of global trade conflicts are questioning the optimism of recent decades concerning the interdependence of our economies. In Germany, this is triggering a discussion about how independent a state or a federation of states must and can be with regard to critical technologies. It becomes clear that there is an increasing conflict between the call for technology sovereignty on the one hand, and the dominant economic model on the other, in which global specialization and the division of labor combined with open trade increases the welfare of all. Germany, in particular, as an export nation, and the EU as an economic area must consider the question of technology sovereignty carefully and in a differentiated manner. We present one conception of technology sovereignty in this position paper. Our intention is to enrich the current debate and improve differentiation. We develop the criteria and key analytical steps needed to determine the criticality of technologies and the degree of technology sovereignty. Building on this, we develop modified strategies to safeguard or to produce technology sovereignty. – – Nicht erst seit der aktuellen Corona-Krise werden die Rufe nach Technologiesouveränität in Europa lauter. Wachsende geopolitische Unsicherheiten und drohende globale Handelskonflikte stellen den Verflechtungsoptimismus der letzten Jahrzehnte in Frage. Dies löst auch in Deutschland eine Diskussion darüber aus, wie unabhängig ein Staat oder ein Staatenbund in Bezug auf kritische Technologien sein muss und sein kann. Dabei wird deutlich, dass die Forderung nach Technologiesouveränität in einem Spannungsverhältnis zum dominanten wirtschaftspolitischen Modell steht, in welchem weltweite Spezialisierung und Arbeitsteilung in Verbindung mit offenen Handelsbeziehungen die Wohlfahrt Aller erhöht. Gerade die Exportnation Deutschland und der Wirtschaftsraum der EU müssen deshalb die Frage nach Technologiesouveränität differenziert und mit Augenmaß bearbeiten. Mit dem Positionspapier stellen wir eine Konzipierung von Technologiesouveränität vor. Damit wollen wir die aktuelle Debatte bereichern und eine bessere Differenzierung ermöglichen. Wir entwickeln Kriterien und notwendige Analyseschritte, um die Kritikalität von Technologien und den Grad an Technologiesouveränität zu bestimmen und darauf aufbauend angepasste Strategien zur Sicherung oder Herstellung von Technologiesouveränität zu entwickeln.
urn:nbn:de:0011-n-5997578
Keywords: 330